Cash flow volatility and capital structure in MENA and Africa: the moderating role of fixed assets - Naser, Abdulrahamn; Bany-Ariffin, A.N.; Matemilola, Bolaji Tunde (Taylor and Francis Group, 2024)
This paper investigates the direct association between cash flow volatility and capital structure (i.e. debt ratio). This study further examines the moderating role of fixed assets on the association between cash flow volatility and capital structure in the Middle East and North Africa (MENA) and African markets. This study applies a two-step system generalized method of moment regression as the main estimation technique to minimize endogeneity concern. The data consist of non-financial listed firms in 20 MENA and African countries covering 2011 to 2020. The results reveal that cash flow volatility is significantly and positively related to capital structure of MENA and African firms. The results also reveal that fixed assets have a negative moderating impact on the relationship between cash flow volatility and the capital structures of MENA and African firms. The results are robust to different estimation techniques. The findings inform managers to consider cash flow stability as a major factor in corporate risk management and strategic decision making and consider fixed asset investment decisions and the quality of fixed assets as a significant factor in debt choice. Moreover, policymakers should formulate efficient capital structure policies that consider cash flow stability factors and encourage fixed asset investments.